PENGARUH MOTIVASI, KOMPETENSI DAN IKLIM KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATA RUANG, PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN KEPULAUAN MERANTI - Rahmi Alyani; Efni Yulia; Rifki Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Performance is the result or level of success of a person as a whole during a certain period in carrying out tasks compared to various possibilities, such as work standards, targets or targets or criteria that have been determined in advance and have been mutually agreed upon. The purpose of this study was to determine the effect of employee motivation, competence and work climate simultaneously on employee performance at the Department of Public Works and Spatial Planning, Housing and Settlement Areas of Meranti Islands Regency. This type of research is descriptive quantitative. The sample in this study amounted to 72 people. Data collection techniques with questionnaires. The data analysis method uses multiple linear regression analysis techniques with the help of SPSS software version 21. The results of the tests that have been carried out show that simultaneously and partially indicate that motivation, competence and work climate have an influence on employee performance (Studies at the Department of Public Works and Spatial Planning, Housing and Settlement Areas of Meranti Regency). Keywords: Motivation, Competence, Work Climate, Performance